1985
DOI: 10.1111/j.1432-1033.1985.tb09252.x
|View full text |Cite
|
Sign up to set email alerts
|

The folding and mutual interaction of the domains of yeast 3‐phosphoglycerate kinase

Abstract: Analysis of the reversible unfolding of yeast phosphoglycerate kinase leads to the conclusion that the two lobes are capable of folding independently, consistent with the presence of intermediates on the folding pathway with a single domain folded. The domains have different free energies of stabilisation. Immunological crossreactivity, circular dichroism and thiol reactivity provide evidence for cyanogen bromide peptide 1 -173, which comprises five-sixths of the N-terminal domain, containing sufficient inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 23 publications
3
28
0
Order By: Relevance
“…In the yeast enzyme a large difference between the calculated and the observed concentration dependence of AG has been reported (a ratio 3: 1 for mcal/mobs) [37]. A ratio of these parameters greater than unity is considered evidence for a significant population of a folding intermediate [40] and it has been suggested that in PGK this species arises through the independent unfolding of one of its domains.…”
Section: Gdnhci Denaturationmentioning
confidence: 99%
See 2 more Smart Citations
“…In the yeast enzyme a large difference between the calculated and the observed concentration dependence of AG has been reported (a ratio 3: 1 for mcal/mobs) [37]. A ratio of these parameters greater than unity is considered evidence for a significant population of a folding intermediate [40] and it has been suggested that in PGK this species arises through the independent unfolding of one of its domains.…”
Section: Gdnhci Denaturationmentioning
confidence: 99%
“…A ratio of these parameters greater than unity is considered evidence for a significant population of a folding intermediate [40] and it has been suggested that in PGK this species arises through the independent unfolding of one of its domains. In the light of the fluorescence transitions observed for PGK [37,38] it would seem likely that the N domain would partially or completely unfold before the more stable C domain. Differentiating the polynomial described by Adams et al [37] using the same fractional exposure of residues as these authors to correct AG, we obtain the values of mca, listed in Table 2.…”
Section: Gdnhci Denaturationmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein concentration was determined spectrophotometrically, using All ~ = 4.95 at 280nm (Adams, cm Burgess & Pain, 1985). subtraction of the normalized background (Guinier & Fournet, 1955):…”
Section: Methodsmentioning
confidence: 99%
“…A fragment (residues 1-173) obtained by cyanogen bromide cleavage (Adams et al, 1985) was reported to refold into a native-like structure but to dimerize, thus precluding further characterization. An engineered version of the complete domain (residues 1-184) was characterized as having a "quasi-native" structure (Minard et al, 1989).…”
Section: Discussionmentioning
confidence: 99%